Draft Annual Plan 1972-73 Union Territory of Pondicherry - Planning Commission (Planning Commission, 1972)
The Union territory of Pondicherry comprises the four regions of Pondicherry, Karaikal, Mahe and Yanam, covering an area of about 470.2 sq. kms. with a population of 4.71 lakhs, according to the provisional figures of the 1971 census. The Pondicherry region (area 290.1 sq. kms.) is on the east-coast, about 160 kms. south of Madras Pondicherry region is not a contiguous area but is interspersed with enclaves of Tamil Nadu. It consists of 267 villages, with a total population of 3.39 lakhs. About 160 kms.
Revenue, Finance, and Planning Department Pondicherry